PERANCANGAN UI/UX DASHBOARD REPORTING PADA PORTAL HALAL.GO.ID MENGGUNAKAN METODE DESIGN THINKING - Anugradia, Nabila; Arsa, Daniel; Khaira, Ulfa (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2024)
The research aims to design a UI/UX dashboard reporting system for the Halal.go.id Portal using the design thinking method. This method involves research stages: Empathize, Define, Ideate, Prototype, and Test. The research employs qualitative methods with observation, interview, and heuristic evaluation techniques. The results indicate that the designed reporting dashboard achieved a score of 358 and a percentage of 89.50% based on 10 heuristic evaluation instruments, falling under the "Very Good" category. This signifies that the reporting dashboard is highly suitable for implementation to improve the UI/UX aspects of the Halal.go.id Portal. This research contributes to the design of effective and efficient UI/UX dashboard reporting for users of the Halal.go.id Portal. The research findings are expected to contribute to enhancing the quality of information services related to halal products in Indonesia.